PARTISIPASI MASYARAKAT DALAM PENDIDIKAN - Wiratno, Budi (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2016)
The purpose of this study: (1) Assess and describe the characteristics of public participation in improving the quality of schools, (2) Assess and describe the efforts of schools to improve community participation, and (3) Assess and describe the forms of public participation in the school. This research is qualitative. The research design chosen in this study is a case study. The place of research in the SDN Jeruk III. Interviewees in this study include Principal and School Committee. Collecting data using observations, interviews and documentation. Interview technique refers to the theory of first order and second order understanding. The validity of the data was tested using triangulation to the source. Analysis using version Milles and Huberman ie by way of data reduction, data and drawing conclusions and verification. The results showed that: (1) The use of open management are the traits of community participation in SDN Jeruk III through a process of community engagement began to plan, define, execute, supervise and conduct participatory evaluation, (2) Promote community participation to build the image of the school, through the use of the characters, hospitality events, through appeal or solicitation, and (3) forms of public participation in the form of participation in the form of financial/material, participation in the form of ideas or the ideas of thought and participation in the form of prayers